Simultaneous K and L-band spectroscopy of Be stars: circumstellar envelope properties from hydrogen emission lines - Granada, Anahi (2010)
We present medium-resolution K- and L-band spectra of a sample of eight Be stars, obtained with Gemini/ NIRI. The IR K and L bands contain many lines of different hydrogen series that are used as a diagnosis to the physical conditions in the circumstellar environments. We make an analysis on the optical depths of the line-forming regions based on the intensity ratios of Pfγ and Brα lines, the behavior of Humphreys’ series, and the fluxes of Brα and Brγ lines. All our targets show spectroscopic and photometric long-term variability; thus, time-resolved K- and L-band spectroscopy is an ideal tool for studying the structure and evolution of the innermost regions of the envelope and to test models on the disk-forming mechanism. We note that the instrumental configuration used allowed us to obtain good quality IR observations and to take profit of Gemini band 3 observing time (allocation time for ranked programs in which the observing conditions are relaxed).